2019
DOI: 10.1111/imig.12572
|View full text |Cite
|
Sign up to set email alerts
|

Do Migrant Remittances Cause Dutch Disease in Nigeria?

Abstract: Statistics show that remittances inflow to Nigeria grew from US$3,000,000 in 1978 to over US$22 billion in 2017. Theoretically, such a large inflow of foreign currency into an economy may lead to Dutch diseases. This study, therefore, investigated whether the massive inflow of remittances into the economy causes Dutch disease. Given that the model had both I(0) and I(1) variables, ARDL/Bound testing methodology was used with annual data from 1981 to 2016. The ARDL result showed that migrant remittances have a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
(31 reference statements)
1
5
0
1
Order By: Relevance
“…Yet, the authors showed that foreign direct investment, government spending and output growth help in reducing exchange rate fluctuations. Likewise, Urama et al (2019) scrutinized the determinants of Nigerian exchange rates volatility and found that economic openness increases Nigeria ERV showing a unidirectional causality running from trade openness to ERV. The study of Razak et al (2020) documented that trade openness has a positive impact on Malaysian ERV.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yet, the authors showed that foreign direct investment, government spending and output growth help in reducing exchange rate fluctuations. Likewise, Urama et al (2019) scrutinized the determinants of Nigerian exchange rates volatility and found that economic openness increases Nigeria ERV showing a unidirectional causality running from trade openness to ERV. The study of Razak et al (2020) documented that trade openness has a positive impact on Malaysian ERV.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study employed unit root exams such as Augmented [17,18]. Table (1) offers the results of unit root checks that all variables are nonstationary at the level and become stationary. The computed fee of F-statistic indicates the confirmation of the association between real superb alternate charge and the rest of the independent variables like migrant remittances, inflation, and GDP per capita exists in the lengthy run because the computed cost is higher than the upper certain values in each model with and barring the interaction term.…”
Section: Results and Discussion Of Findingsmentioning
confidence: 99%
“…Temporary migrants encompass contract workers, inter-agency transferees, students, and businessmen whilst irregular people are those who continue to be in remote places illegally or on an expired visa on traveling. From Figure (1), we can see an inclining vogue of laborers' remittances and compensation of employees, which received a share of GDP from 12 months 1984 (1%) until it reached the peak in 2005 (19%). Since then, it diminished to 8% in 2011.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sin embargo, no faltan investigaciones que alertan sobre una posible relación inversa entre esas variables (Giuliano y Ruiz-Arranz, 2009;Catrinescu et al, 2009) y en algunos casos se han explicado también las causas (Chami, Fullenkamp y Jahjah, 2005;Chami et al, 2008;Alonso y Sovilla, 2014). La principal razón de esta relación contra-intuitiva entre remesas y crecimiento económico en el país receptor es la enfermedad holandesa, fenómeno que ha sido objeto de varios estudios econométricos, sobre todo en economías en vía de desarrollo de América Latina, Asia y África (Faheem et al, 2022;Roy y Dixon, 2016;Chnaina y Makhlouf, 2015;Urama, Edeh y Urama, 2019;Owusu-Sekyere, Koekemoer Van Eyden y Kemegue, 2014). En este artículo investigamos el problema de la enfermedad holandesa atribuible a las remesas, pero desde un enfoque metodológico distinto que inserta las remesas en modelos macroeconómicos (Glytsos, 2005;Loser et al, 2006;Alonso y Sovilla, 2014;Rashid y Sharma, 2017).…”
unclassified